The Correlation Of Standard Precautions Knowledge Level With Covid-19 Cases That Have Occurred In Dental And Oral Therapists - Agnes Lia Renata; Suharyono Suharyono; Furaida Khasanah (Jurnal Kesehatan Prima, 2023)
COVID-19 cases continue to spread in every level of society, including dental and oral therapists. The dental and oral therapist's work zone that is in contact with droplets and saliva is the transmission of COVID-19 transmission. Prevention of transmission of COVID-19 to dental and oral therapists is carried out through the application of standard precaution which is influenced by the level of knowledge of each individual. Lack of knowledge causes a person to have poor standard precaution applications. To determine the relationship between the level of knowledge of standard precaution with the application of standard precaution to dental and oral therapists in preventing the transmission of the COVID-19 virus.This research is an analytic survey with a cross sectional design. The study was carried out in January-February 2022. Sampling using proportionate stratified random sampling technique with a sample of 130 people. Data analysis using Kendall’s tau. The results showed a p-value of 0.00 (p<0.005). Test (t) = 0.419. Most of the respondents have a moderate level of knowledge (38.5%), while the level of application of standard precaution is mostly in good criteria (66.9%). The level of knowledge of standard precaution is related the application of standard precaution of dental and oral therapists in preventing the transmission of the COVID-19 virus with a fairly strong positive correlation.